KIPRAH POLITIK KOMUNITAS MENUJU GOOD GOVERNANCE - Tetty Deliani (Universitas Medan Area, 2016)
This paper seeks to examine the process of political reform and progress toward the community of good governance through the realization of new ideas and perubahan.Asumsinya is that reforms in that direction would be done by reference, the values of autonomy and democracy itself. The main agenda of the reform is decentralization and democratization of governance. Ideal conditions to be achieved by the second groove terlembaganya reform is a good governance at all levels of government, which berpilarkan principles of democracy and autonomy. Since the issues addressed in this paper always involves the concepts, the paper is not purely empirical. Even so, the presentation of empirical effort as possible.